Philadelphia’s Historical Maps and Green Initiatives - Wingert-Playdon, Kate (ARCC Conference Repository, 2014)
The ‘Greene Countrie Towne,’ William Penn’s seventeenth century vision for Philadelphia, has served as the spatial framework for the city throughout its history. Penn’s settlement in the New World in the 1680s was focused on equality and religious freedom. The city layout reflected and housed his ideal settlement. Throughout history, the initial city plan has been a central force guiding Philadelphia’s urban imagination. Penn’s vision of a ‘Greene Countrie Towne’ is responsible for initiating and driving idea of ‘green’ that characterize Philadelphia. With Penn’s plan and vision as guide, Philadelphia’s ideas of ‘green’ along with the city’s green infrastructure have developed over time and have served as a driver of Philadelphia’s identity. This paper outlines the thread that links Philadelphia’s initial plan and vision to the current day. Current planning and policy initiatives for Philadelphia include a new idea of ‘green,’ a focus on the sustainable city and a pledge by Philadelphia’s mayor to become the country’s greenest city by 2015. William Penn’s city vision and plan continue to guide the city’s consciousness and initiatives. The reflective quality of the sustainable city, directly linked to the ‘green’ vision for Philadelphia, has the potential to impact the urban imagination in a new and innovative manner while building on the historical thread that links back to the vision of the ‘Greene Countrie Towne.’